Kinetics and Mechanism of Reactions of Aliphatic Stable Nitroxide Radicals in Chemical and Biological Chain Processes - Pliss, Eugene M.; Tikhonov, Ivan V.; Rusakov, Alexander I. (IntechOpen, 2012)
None